Outcomes of On- Versus Off-Pump Coronary Artery Bypass Grafting for Acute and Subacute Myocardial Infarction: A Nationwide Propensity Score-Matched Cohort Study - Hyo-Hyun Kim; Jiyoung Shin; Kang Ju Son; Kyung-Jong Yoo; Young-Nam Youn (Journal of Clinical Medicine, 2026)
Background/Objectives: The comparative efficacy of off-pump and on-pump coronary bypass grafting (CABG) for patients with acute and subacute myocardial infarction (AMI) remains controversial. We compared the outcomes of on-pump versus off-pump coronary artery bypass grafting in Korean patients with acute and subacute myocardial infarction. Methods: This nationwide retrospective cohort study included 14,578 propensity score-matched patients undergoing on-pump or off-pump CABG between 2007 and 2022 using the Korean National Health Insurance Service database. The primary outcomes were recurrent myocardial infarction, repeat revascularization, stroke, all-cause mortality, and major adverse cardiovascular and cerebrovascular events. Chi-square, Kaplan–Meier, and log-rank tests and Cox regression analysis were used. Results: Compared with on-pump CABG, off-pump CABG was associated with significantly lower risks of major adverse cardiovascular and cerebrovascular events (MACCEs), all-cause mortality, and recurrent myocardial infarction in the cause-specific Cox analysis, whereas repeat revascularization and stroke rates were comparable between groups. However, the association with recurrent myocardial infarction was not statistically significant in the Fine–Gray competing-risk analysis. Conclusions: Off-pump CABG was associated with lower risks of all-cause mortality and MACCEs in patients with acute and subacute myocardial infarction. The association with recurrent myocardial infarction was less consistent across analytical approaches and should be interpreted cautiously.